Two new genera and species of fossil true bugs (Hemiptera: Heteroptera: Pachymeridiidae) from northeastern China - Lu, Ying; Yao, Yunzhi; Ren, Dong (Zootaxa, 2011)
Two new genera and new species, Peregrinpachymeridium comitcola gen. et sp. nov. and Corollpachymeridium heteroneurus gen. et sp. nov., of fossil Pachymeridiidae are described and illustrated from the Middle Jurassic Jiulongshan Formation in Daohugou Village, Shantou Township, Ningcheng County, Inner Mongolia Autonomous Region, China. We summarized all fossil genera of pachymeridiids found in China and set up a key to these 7 genera and 7 species. In addition, we hypothesize the significance of a rare, well-preserved, unusual bug fossil showing a male and a female together with their abdomen terminalia facing each other and their heads in the opposite direction.